Effectiveness of Post National Dose Survey (NADs1) Towards Dose Compliance Level. (March 2020) - Kayun, Z.; Karim, M.K.A.; Shaari, A.H.; Mahmud, R.; Rahmat, S.M.S.
Abstract: The increasing number of CT procedures owing to advanced CT technology requires careful monitoring by the personnel involved to ensure appropriate examinations and optimized procedures. For that reason, CT optimization is a crucial factor that could help to compensate for [[[AUTHOR: Could this sentence be clarified with more specific information? For example, you might say that optimization compensates for the poor image quality that can occur with low radiation. Thank you.]]] radiation dose and image quality. In current practice, optimization in CT is a complex procedure due to a wide range of acquisition parameters in imaging protocols. Diagnostic Reference Levels (DRLs) have been defined by the International Commission on Radiation Protection (ICRP) as a form of investigating the level of patient dose for a specified procedure used in medical imaging to indicate whether, in routine conditions, the patient dose is unusually high or low for that procedure. Hence, the Ministry of Health (MOH) has established a national DRL through a dose survey conducted from 2007 to 2009, and the project is called as NADS1. However, the study does not cover the effectiveness of image quality; in contrast, the current research focuses on both dose exposure and image quality to determine the level of effectiveness of the developed NADS1 data. This study involves several levels, including the acquisition of patient exposure data, image quality assessment, and effective dose measurement. Determination of acquisition of patient exposure data is based on the indicator of QAP CT Brain developed by the MOH, i.e., the total number of adult CT brain examinations for which the DLP value shall not exceed 10% of the national DRL values, 1050 mGy.cm. The outcome of this study can be used as a measure to optimize patients' radiation exposures and can be a guide for implementing improvement measures. The results of this study allow radiology personnel to understand the concepts and mechanisms associated with managing patient radiation exposures. The outcome also provides the level of effectiveness of the developed QAP, which was implemented by the MOH and subsequently became a benchmark for improving the quality of healthcare services. Therefore, it is clear that this study has shown an impact on the level of optimization from the radiation exposure study, the NADS2 that is being implemented.